Feeling Safe on the Train: Gendered Perspectives on Security in the Jabodetabek Commuter Line - Arya Mayadi (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
Public transportation is a critical element of urban mobility, yet perceptions of safety often vary across gender. In Jabodetabek, the KRL Commuter Line serves millions of passengers daily, providing essential connectivity but also raising concerns about harassment, overcrowding, and unequal access to secure spaces. This study explores how male and female commuters perceive and experience safety while using the KRL, with attention to both physical security and psychological comfort. Data were collected through in-depth interviews with ten regular KRL users, supported by field observations and another publication discussing perceptions and security on the Jabodetabek commuter line. Using a gendered perspective, an analysis was then applied to examine differences in gendered perceptions, self-regulatory behavior strategies employed to achieve a sense of security, and the effectiveness of women-only carriages. The findings reveal notable differences in safety perceptions between male and female KRL passengers. Female passengers often report discomfort when traveling in mixed carriages with male passengers, particularly in situations where close physical contact is unavoidable due to overcrowding. Such proximity can evoke feelings of fear and unease, leading to heightened vigilance during travel. In contrast, male passengers generally do not perceive close contact in crowded carriages as problematic. Consequently, many female passengers opt for women-only carriages as a preferred strategy to mitigate feelings of insecurity and enhance their sense of safety. The study underscores the role of women-only carriages in fostering a sense of safety for female passengers within Jabodetabek’s urban mobility network. Nevertheless, these dedicated carriages are not without challenges, as instances of more assertive or aggressive passenger behavior are reported to occur more frequently compared to mixed carriages.